Effects of clinical decision topic on patients’ involvement in and satisfaction with decisions and their subsequent implementation - Freidl, Marion; Pesola, Francesca; Konrad, Jana; Puschner, Bernd; Kovacs, Attila; De Rosa, Corrado; Fiorillo, Andrea; Krogsgaard Bording, Malena; Kawohl, Wolfram; Rössler, Wulf; Nagy, Marietta; Munk-Jørgensen, Povl; et al. (American Psychiatric Publishing, 2016)
Clinical decision-making is the vehicle for mental health care delivery, and predictors of decision-making experience and adherence are under-researched. The aim was to investigate the relationship between decision topic and kind of involvement in the decision, satisfaction and subsequent implementation, from both staff and patient perspectives.